URBAN LIVING SPACE: BANDUNG PUBLIC LIBRARY - ELIZABETH SORTA (NIM : 15213079), EUNIKE
Library is one of another type of public space that functionate as a source of knowledge and information. Along with the developing era, the consumption of gadget especially smartphone is also increasing. The use of smartphone makes a switch role for books, they are not longer used as a source of knowledge and information. This phenomenon degrades the real purposes of library and also their visitors. Beside that, globalization era is causing consumptive behaviour that makes people tend to go to shopping malls and buying things they actually do not need than going outside and enjoying public space that Bandung has provide it well with mild and pleasant climate. From this situation, there is a need for library to change so it can adjust the situation of this era. The answer to this problem, library needs to provide another space besides to read and study like the addition of commercial space and also a public space. Library needs to appeal people in the urban area so they will become interested to come besides to read or study because actually they can do more like buying something or even playing. The attraction of library not only helping to increase reading interset but also can be the real public space that can be accessed by everyone and becomes a place for all urban people to enjoy as a living space.